LIFE CYCLE ASSESSMENT IN SUPPLY CHAIN MANAGEMENT GAME - Hartono, Natalia; Laurence, Laurence; Chandra, Giovanni Hezekiah (UI Scholars Hub, 2020)
Educational games are essential in explaining theories to students as such activities create a fun learning environment. Most educational games in supply chain management (SCM) are focused on SCM or logistics theories. In the last decades, the research in environmentally conscious SCM has increased. However, the educational games related to such SCM are limited. This work is the first to use the detailed life cycle assessment (LCA) approach in teaching students SCM. The research output is a game called “Robo Factory,” which involves a simulation of a robot production supply chain. The research objective is to educate undergraduate students about the SCM structure, the duties and responsibilities of SCM actors, the LCA approach, and the cost types in SCM and LCA. The paper describes the game design process. The game design entails three steps: (1) game conceptualization and prototype design; (2) prototype trial, evaluation, and finalization of game rules; and (3) final games. Evaluation results indicate that the game successfully teaches undergraduate students about the theory of LCA in SCM in an enjoyable manner. The posttest shows an overall increase in students’ knowledge. The paper presents the future research directions and implications for scholars to enhance their contributions.